PS 14-32 CURRENT PRESCRIPTION STATUS OF DIURETICS IN THE JAPANESE HYPERTENSIVE PATIENTS. (September 2016) - Ibaraki, Ai; Goto, Wataru; Iura, Rie; Tominaga, Mitsuhiro; Tsuchihashi, Takuya
Abstract : Objective: The guideline for the management of hypertension recommends the inclusion of diuretics especially when three or more antihypertensive drugs are used. Design and Method: The prescription including antihypertensive drugs were collected in the dispensing pharmacy belonged to the Yawata Pharmacist Association, located in Kitakyushu City, in October, 2014. Prescriptions for diabetes, dyslipidemia, and hyperuricemia and the use of antithrombotic drugs were also investigated. Results: Among 10585 prescriptions, calcium channel blockers (CCB) were prescribed in 73.5% of the subjects, followed by angiotensin II receptor blockers (ARB, 62.7%), diuretics (16.5%), and beta-blockers (13.6%). The number of prescribed antihypertensive drugs was 1.80.The combination of CCB and ARB was the most frequent prescription pattern in the patients with taking two antihypertensive drugs (N = 4158) and the prescription of diuretics remained low (13.1%). The prescription rates of diuretics in the patients with single drug, two and three drugs were 1.6, 13.1 and 55.2%, respectively. The average number of the antihypertensive drugs who were taking diuretics was 2.93. A 40% of the patients with diuretics were prescribed as combination tablets of hydrochlorothiazide with ARB, while trichlormethiazide (34.9%) and indapamide (19.8%) were used in the other patients. Conclusions: The prescription rate of diuretics was 16.5% among 10585 Japanese hypertensive patients. The use of diuretics is still limited even in the patients taking three antihypertensive drugs.